(untitled) (Journal of Engineering, 2013)
Al Huweizah Marsh is considered as the largest marsh at the southern part of Iraq. About one third of the marsh is located within the Iranian territory. Iran began to construct earth dikes along the Iraqi-Iranian international borders to separate the Iranian part of the marsh. The electrical conductivity, EC, value was adopted to be the indicator for the water salinity within the marsh. A steady two-dimensional water quality routing model was implemented by using the RMA2 and RMA4 softwares within the SMS computer package to estimate the distribution of the EC values within the marsh seasonally during the wet, moderate and dry water years. The EC distribution Patterns were estimated considering the expected two cases of the marsh future hydrological and geometrical conditions of the marsh, Case 1: without existence of the earth dikes and Case2: with the existence of the earth dikes. The estimated distribution patterns of EC values showed that the construction of the earth dikes, Case2, deteriorate the water salinity within most of the Iraqi part of the marsh during the four seasons of the wet, moderate and dry water years. During the wet and moderate years, the EC values are greater than the maximum allowable limits within most of the Iraqi part of the marsh except small portions near the outfall of the Iraqi feeders of the marsh and the lower portion of the southern part of the marsh during winter of the moderate years. While during the four seasons of the dry years, the marsh water is stagnant and the EC values are much greater than the maximum allowable limits.